Evaluation of body mass index in patients with dipper and non-dipper hypertension - Memioğlu, Tolga; İnanır, Mehmet and Argana, Kıvanç and Kiriş, Salih Vahit and Güven, İbrahim and Dıramalı, Murat and Toprak, Kenan and Özyaşar, Mehmet (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCircadian variation in blood pressure, particularly the distinction between dipper and non-dipper profiles, plays a critical role in cardiovascular risk stratification. Although recent studies suggest that obesity may contribute to non-dipping patterns, the relationship remains controversial.ObjectiveTo compare body mass index (BMI) between dipper and non-dipper hypertensive patients and to evaluate whether BMI can serve as a marker of non-dipping status.MethodsThis retrospective observational study analyzed ambulatory blood pressure monitoring (ABPM) records of 200 patients (100 dippers and 100 non-dippers) who underwent 24-h ABPM using a validated Holter device. BMI values were calculated and compared between groups.ResultsThe distribution of sex did not differ significantly between dipper and non-dipper patients (p = 0.571). The mean BMI was significantly higher in the non-dipper group compared with the dipper group (30.75 ± 5.42 vs. 28.07 ± 5.09 kg/m2, p = 0.002). Non-dipper hypertensive patients demonstrated significantly higher BMI levels than dipper patients.ConclusionsThese findings support the hypothesis that obesity may impair nocturnal blood pressure regulation and suggest that BMI could serve as a simple marker of non-dipping status. This indicates a potential association between increased BMI and a non-dipping blood pressure profile. Due to its retrospective design, this study cannot establish causality.